The development of English plural expressions among Malaysian kindergarten children. - Syed Uzir, Sharifah Fatin Athira; Mohamed Salleh, Rabiah Tul Adawiyah (2020)
English is a strong second language in Malaysia, reflected in its importance in education, governance and popular culture (Hashim, 2014). In Malaysia, children learn English as early as at 4 years of age. However, it is unknown how Malaysian children acquire English in a Malaysian context as studies investigating early English development is scant. Therefore, this study intends to investigate the development of English, specifically looking at English plural expressions among Malaysian kindergarten children. Additionally, this study also investigates the effectiveness of developmentally moderated focus-on-form (DMFonF) instruction on learning English plurals in the Malaysian context within 6 months. The participants in this study will be six kindergarten children from two preschools under the Ministry of Education. They will be divided into two groups: group A and group B. The developmentally focus-on-form instruction will be introduced to group A by their teachers through their English lessons throughout the period of study. Meanwhile, group B will continue their lessons without any intervention. At the beginning of the study, a pretest will be administered to establish the children’s English baseline (T1) and after 6 months, a posttest will be administered (T2). The data from the pretest and posttest will be both audio and video recordings. Afterwards, the development of plural expressions between group A and group B will be analysed and compared. Based on previous research by Hardini, Kawaguchi, Reid, and Di Biase (2019), the findings might indicate that the plural expressions of children in group A who receive the DMFonF instruction will develop significantly faster compared to that of children in group B who do not receive the DMFonF instruction in their English lessons.